2017
DOI: 10.1093/bja/aex098
|View full text |Cite
|
Sign up to set email alerts
|

Financial and environmental costs of reusable and single-use anaesthetic equipment

Abstract: For an Australian hospital with six operating rooms, converting from single-use to reusable anaesthetic equipment saved more than AUD$30 000 (£18 000) per annum, but increased the CO 2 emissions by almost 10%. The CO 2 offset is highly dependent on the power source mix, while water consumption is greater for reusable equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 17 publications
3
100
0
3
Order By: Relevance
“… Face masks, circuits and laryngoscope blades. Known: Using reusable anaesthetic equipment estimated to save AUD$5000/OR/annum 91 ; however, in Australia, using reusable equipment can have a slightly higher carbon footprint than single-use. Conversely in Europe/UK/USA the carbon footprint is much lower for reusable equipment (more renewable electricity).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Face masks, circuits and laryngoscope blades. Known: Using reusable anaesthetic equipment estimated to save AUD$5000/OR/annum 91 ; however, in Australia, using reusable equipment can have a slightly higher carbon footprint than single-use. Conversely in Europe/UK/USA the carbon footprint is much lower for reusable equipment (more renewable electricity).…”
Section: Discussionmentioning
confidence: 99%
“… 72 , 75 , 84 An Australian LCA comparing reusable and single use anaesthesia devices such as face masks, rigid and videolaryngoscope handles and blades, and breathing circuits 91 found that reusable equipment saved approximately AUD$5000 per operating room (OR) p.a. ; however, the carbon footprint was higher (about 100 kg CO 2 e emissions per OR p.a., 91 equivalent to 800 km yr −1 driven in an average UK car). 92 If the reusables had been washed and sterilised in Europe, the carbon footprint of reusable anaesthetic equipment would have been less by 800 kg CO 2 e emissions per OR p.a.…”
Section: Life Cycle Assessments In Anaesthesia and Critical Carementioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that reusable devices were more favorable financially as well as from an environmental viewpoint. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%